Impossible, yet not problematic: Making sense of adoption with dialogic type theory - Álvarez Lisboa, Miguel (2021)
Logical laws cannot be adopted —so goes Kripke and Padró’s Adoption Problem. Their argument can be seen as an invitation to revisit the way in which we relate Logic and inferential practice. For them, the former does not come before, but after the latter. In this paper I delve into this conclusion by showing how the impossibility of adoption can be naturally associated with some features of Immanent Reasoning, which is a mix between Dialogic and Constructive Type Theory that incorporates the pragmatics of inference at its core. The major insight to be drawn from this approximation is that adoption, although not possible, is no longer needed. Subsequently, the ‘problem’ loses its ‘problematic’ character. This conclusion illustrates some of the advantages of favoring the game-theoretic approach to semantics in philosophical logic.